Does variety of social interactions associate with frequency of laughter among older people? The JAGES cross-sectional study. Issue 1 (7th January 2021) - Nagai, Masato; Ohira, Tetsuya; Shirai, Kokoro; Kondo, Katsunori
Abstract : Objective: Several studies have reported that laughter is associated with health benefits. In addition, social interactions, such as social relationships, social participation and so forth, have shown the association with not only health but also individual emotion. In this study, we conducted a cross-sectional study to examine the association between variety of social interactions and the frequency of laughter. Design: Cross-sectional study. Setting: Sampled from 30 municipalities in Japan. Participants: Non-disabled Japanese men (n=11 439) and women (n=13 159) aged ≥65 years using data from the Japan Gerontological Evaluation Study, which was conducted during October to December in 2013. Primary outcome measures: Laughing almost every day by self-reported questionnaire. Results: Poisson regression analysis with robust error variance was used to calculate prevalence ratios (PRs) for laughing almost every day according to each social relationship and its potential community-level environmental determinants. The prevalence of laughing almost every day tended to increase with increased variety in each social interaction after adjusting, instrumental activities of daily living, number of living together, working status, depression, self-reported economic status and residence year. Among men and women, multivariate-adjusted PRs (95% CIs) by comparing participants with the highest and lowest categories were 1.18 (1.04 to 1.35) and 1.16 (1.04 to 1.29) in positive life events; 1.26 (1.10 to 1.45) and 1.09 (0.96 to 1.24) in perceived positive changes in the area; 1.15 (1.04 to 1.28) and 1.17 (1.07 to 1.28) in social participations; 2.23 (1.57 to 3.16) and 1.47 (1.02 to 2.12) in social relationships and 1.25 (1.08 to 1.45) and 1.29 (1.15 to 1.45) in positive built environments. These associations were also preserved after the restriction of participants who were not in depression. Conclusions: This study shows that a greater variety of each social relationships and the potential community-level environmental determinants are associated with higher frequencies of laughter in Japan.